The discourses and literacy practices of doing science in English - Revathi Ramiah,; Koo, Yew Lie; Jamilah Mustafa, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
In January 2003, Malaysia re-adopted the English language as a medium of instruction for science and mathematics. This change in the medium of instruction brings with it challenges of its own. What does it mean to ‘do’ science in the Malaysian context and to do so in English? How does the change in the medium of instruction from Bahasa Malaysia to English impinge upon the instructional and literacy practices of teachers and learners? What kinds of changes are required of the communities and stakeholders involved in the teaching of science? This article will address these questions by critiquing some dominant assumptions behind the literacy practices of ‘doing’ science in the Malaysian context based upon the findings of a qualitative case study conducted to investigate how two teachers working in diverse and different contexts in Malaysian schools cope with the new medium of instruction